Reliability, validity and responsiveness of the Chester step test in people with Interstitial Lung Disease - Alves, Ana Queiroz (2020)
The Chester step test (CST) is a simple and inexpensive field test, which requires minimal physical space to assess exercise tolerance. Such characteristics make the CST suitable to be used in different settings, however, its clinimetric properties in people with interstitial lung diseases (ILD) are unknown. Aim: To assess the reliability, validity, responsiveness and learning effect of the CST in people with ILD. Methods: An observational descriptive study was conducted in people with ILD recruited from routine pulmonology appointments. Participants were asked to attend to 2 assessment sessions, with 48-72 hours apart and with the presence of a 2nd rater in one of the sessions. In the first session CST-1 and 6-minute walk test (6MWT-1) were performed. In the second session, the CST-2 and the following patient-reported outcome measures (PROMs) were applied: modified Medical Research Council (mMRC) questionnaire, COPD assessment test (CAT), St. George’s respiratory questionnaire (SGRQ) and functional assessment of chronic illness therapy-fatigue scale (FACIT-FS). After a 12-week community-based pulmonary rehabilitation (PR) programme, the CST-3, the 6MWT-2 and all PROMs were applied. Relative reliability was measured using intraclass correlation coefficient (ICC1,1 and ICC2,1). Absolute reliability was determined by calculating the standard error of measurement (SEM), the minimal detectable change at 95% confidence interval (MDC95) and Bland&Altman method. The values of SEM and MDC95 were also expressed as a percentage of the mean. Construct validity was explored using Spearman correlation coefficient (rs) between the number of steps taken in the best CST and the distance covered in 6MWT-1. Responsiveness was established by calculating the effect size (ES), the mean difference of steps between CST-1 and CST-3 and the Spearman correlation coefficient between changes in the CST and changes in the 6MWT, mMRC, CAT, SGRQ and FACITFS before and after the PR programme. The learning effect was explored with Wilcoxon Ttest to compare the CST-1 and CST-2. Results: 66 patients with ILD (65.5±12.9 years; 48.5%men; FVC 79.4±18.8pp; DLCO 49.0±18.3pp) participated in the study. Relative reliability was excellent (ICC 0.95-1.0), as well as absolute reliability without evidence of systematic bias. The SEM and MDC95 were 11.8 (14.7%) and 32.6 steps (40.7%), respectively. The correlation between CST-1 and 6MWT-1 was significant, positive and high (rs=0.85, p=0.00). The ES was large (ES=0.49) and the mean difference between CST-1 and CST-3 was significant (12.6±30.7 steps; 95%CI 1.8-23.5; p=0.004). The correlations between changes in the CST and changes in the mMRC and FACIT-FS were significant and moderate (rs=-0.37 and 0.60, p=0.00- 0.036). No other significant correlations were found. There was no statistically significant difference CST-1 and CST-2 (p=0.055). Conclusion: The CST seems to be a reliable, valid, responsive test with no learning effect test to evaluate exercise tolerance in people with ILD.